Preliminary findings on the effect of the pig appeasing pheromone in a slow releasing block on the welfare of pigs at weaning. Issue 1 (December 2016) - Temple, Déborah; Barthélémy, Héloïse; Mainau, Eva; Cozzi, Alessandro; Amat, Marta; Canozzi, Maria; Pageat, Patrick; Manteca, Xavier
Abstract The pig appeasing pheromone (PAP) applied in spray has shown to be effective in reducing the frequency of aggression and the stress response of young and adult pigs under experimental conditions. This preliminary experiment investigates the effect of the PAP in a slow releasing block on the behaviour and skin lesions of weaners after mixing on a commercial farm. Two identical rooms containing six replicates per treatment of a commercial weaner building were used. There were two treatments (PAP block and Control) and each room contained one treatment. In the PAP treatment, the day before weaning and after washing and disinfection, two PAP blocks (1 block / 20 m2 ) were placed hanging on top of the pens. Six hours after mixing, there was a significant effect of the PAP block treatment on the occurrence of social negative behaviour (PAP mean; median [95 % CI] for median = 3.6; 2.7 [1.5-5.4] % vs. Control 8.3; 8.7 [6.1-11.3] %P = 0.003, social positive behaviour (PAP 5.5; 5.1 [4.5-6.8] % vs. Control 1.4; 1.3 [0-2.8] %P = 0.02), feeding (PAP 9.1; 7.4 [5.5-16.5] % vs. Control 1.6; 0.0 [0-6.1] %P = 0.02, drinking (PAP 3.1; 2.9 [2.5-3.9] % vs. Control 0.8; 0.5 [0-1.7] %P = 0.04) as well as on the sitting position (PAP 1.2; 0.9 [0-2.4] % vs. Control 4.1; 4.2 [2.1-6.0] %P = 0.02). Except for social positive behaviour (PAP 5.6; 6.0 [3.9-7.5] % vs. Control 2.9; 2.8 [1.6-4.2] %P = 0.02) those differences were not significant 24 h post-mixing anymore. The prevalence of wounded animals was not significantly different between treatments. The PAP in block form may be a promising tool to reduce food neophobia and aggression after mixing. Still, further research is needed to increase the effect of the PAP block over time under commercial farming conditions.